Juridical Analysis of the One Month Notice Provision for Employee Resignation: A Balance between Workers’ Rights and Company Operational Protection - Candra Robasa Sijabat; Bestari Nirmala Santi; Otto Sumaryoto; Sugeng Santoso PN (Jurnal Ketenagakerjaan, 2026)
The provision regarding worker resignation with a 30 (thirty) day or one-month notice has long been regulated in Indonesian labor laws. This provision aims to ensure legal certainty for workers while safeguarding the continuity of company operations. However, in practice, the application of the one-month notice often raises debates regarding its effectiveness and proportionality. This issue becomes more significant when the resignation involves workers in strategic positions. This study aims to analyze the effectiveness of the one-month notice provision in ensuring legal certainty for workers and in protecting company operations based on labor regulations in Indonesia. The research uses a normative legal research method with a statutory and conceptual approach. The analysis is based on the theory of legal certainty and the theory of balance of interests. The results of the study show that, normatively, the one-month notice provision has provided procedural legal certainty for workers, particularly in relation to the fulfillment of administrative and normative rights. However, this provision has not been fully effective in protecting company operations, especially when workers in strategic positions resign. In such cases, the standard notice period may not provide sufficient time for companies to prepare operational adjustments. Therefore, efforts are needed to harmonize the regulation through a more flexible and proportional arrangement of the resignation notification period. One possible approach is to diversify the notice period based on job characteristics, urgency, and the potential operational impact. This approach is expected to create a better balance between workers' rights and the sustainability of company operations in a fair and sustainable manner.